Case Report: A rare presentation of vascular Ehlers-Danlos syndrome with a massive hemothorax and a chest wall hematoma - Han, Beisi; Li, Su; Ye, Yutian; Lu, Xiaoyu; Zhang, Heng (Frontiers in Medicine, 2025)
BackgroundVascular Ehlers-Danlos syndrome (vEDS) is a rare but life-threatening subtype of the Ehlers-Danlos syndromes (EDS), a group of inherited connective tissue disorders with significant clinical and genetic heterogeneity. vEDS is mainly caused by mutations in the COL3A1 gene, leading to type III collagen abnormalities. vEDS is characterized by increased vascular fragility and predisposition to serious complications such as arterial rupture and gastrointestinal perforation. However, vEDS cases with hemothorax as the primary manifestation are extremely rare and are easily misdiagnosed or underdiagnosed.Case presentationWe report a 28-year-old man who was admitted to the hospital with a sudden onset of right-sided chest and back pain. Imaging examinations and thoracentesis revealed a massive right-sided hemothorax and a right posterior chest wall hematoma. The patient had a medical history of two episodes of spontaneous pneumothorax, as well as arterial aneurysms and dissections, along with a family history of major arterial rupture. After admission, his hemoglobin level progressively declined, which stabilized following right intercostal artery embolization. Genetic testing ultimately identified a heterozygous COL3A1 mutation, confirming the diagnosis of vEDS.ConclusionIn this case, the patient presented with a massive right-sided hemothorax and a large chest wall hematoma without any obvious precipitating factors, in the absence of other typical clinical manifestations of vEDS, such as gastrointestinal perforation, which increased the diagnostic challenge. Possible pathogenic mechanisms include type III collagen abnormalities leading to increased fragility of the subpleural vessels, triggering vascular rupture. Clinically, young patients with recurrent hemothorax or multiple arterial lesions should be kept on high alert for early genetic testing to clarify the diagnosis and optimize management. This case helps to raise awareness of the heterogeneous clinical manifestations of vEDS and to avoid misdiagnosis and underdiagnosis.